Effects of Medical Therapy on Mild Obstructive Sleep Apnea in Adult Patients - Smith, David F. (J Clin Sleep Med, 2019)
STUDY OBJECTIVES: Patients with obstructive sleep apnea (OSA) have been shown to have high levels of inflammatory markers. Anti-inflammatory treatment with montelukast and intranasal steroids have demonstrated efficacy for mild OSA in children; this has not been fully evaluated in adults. This study investigated the response of mild OSA in adults to anti-inflammatory medical therapy. METHODS: Adults aged ≥ 21 years with an apnea-hypopnea index (AHI) ≤ 15 events/h on polysomnography (PSG) were recruited to a prospective double-blind, randomized control trial. Patients were treated for 12 weeks with montelukast and fluticasone or placebo. All underwent a pretreatment and posttreatment PSG. Epworth Sleepiness Scale (ESS) score was obtained pretreatment and at 6 and 12 weeks posttreatment. RESULTS: A total of 26 patients completed the study with 13 in each group. Mean age in the treatment and placebo groups were 58.3 ± 10.3 and 54.8 ± 14 years, respectively. There was no significant difference between groups reporting nasal congestion (P = .186), rhinitis (P = .666), or snoring (P = .177). There was no difference in the pretreatment ESS score (P = .077), body mass index (P = .173), or AHI (P = .535). The posttreatment PSG in the treatment group demonstrated a significant increase in total sleep time (P = .02) and percent of stage R sleep (P = .05). Neither group showed significant change in AHI. In patients in the treatment group, the 6- and 12-week follow-up ESS scores were not significantly different from pretreatment scores (P = .37–.46). CONCLUSIONS: Intranasal steroids and montelukast did not decrease AHI; however, total sleep time and percent of stage R sleep significantly increased. Self-reported improvement could be explained by observed changes in sleep parameters. Larger prospective studies could help elucidate the effects of medical therapy on adult patients with OSA. CLINICAL TRIAL REGISTRATION: Registry: ClinicalTrials.gov; Title: Montelukast and Nasa ICS for Treatment of Mild Obstructive Sleep Apnea in Adults; Identifier: NCT01089647; URL: https://clinicaltrials.gov/ct2/show/record/NCT01089647 CITATION: Smith DF, Sarber KM, Spiceland CP, Ishman SL, Augelli DM, Romaker AM. Effects of medical therapy on mild obstructive sleep apnea in adult patients. J Clin Sleep Med. 2019;15(7):979–983.